2021
DOI: 10.2196/25202
|View full text |Cite
|
Sign up to set email alerts
|

The Nature and Extent of Online Marketing by Big Food and Big Alcohol During the COVID-19 Pandemic in Australia: Content Analysis Study

Abstract: Background Emerging evidence demonstrates that obesity is associated with a higher risk of COVID-19 morbidity and mortality. Excessive alcohol consumption and “comfort eating” as coping mechanisms during times of high stress have been shown to further exacerbate mental and physical ill-health. Global examples suggest that unhealthy food and alcohol brands and companies are using the COVID-19 pandemic to further market their products. However, there has been no systematic, in-depth analysis of how “… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 22 publications
6
35
0
Order By: Relevance
“…The COVID-related themes commonly used by unhealthy food and drink brands in social media posts were analogous to those found in studies globally (17,31), with "community support, " positioning themselves as "in this together" with consumers, and "applauding health staff and front-line workers" common narratives. A similar study in Australia found the same level of COVID-washing in social media posts, whereby one-third of all posts by the "Big Food and Drinks" brands during the same 4-month period were COVID-19 related, and fast-food companies were also the largest proponents of COVID-washing (31). The COVID-19 pandemic provided an opportunity for food and beverage companies to market themselves as caring and contributing members of a society during a time of unprecedented crisis, and thereby increase the desirability of their brands and the products they sell.…”
Section: Covid-washing By New Zealand's Major Food and Drinks Brandssupporting
confidence: 52%
See 4 more Smart Citations
“…The COVID-related themes commonly used by unhealthy food and drink brands in social media posts were analogous to those found in studies globally (17,31), with "community support, " positioning themselves as "in this together" with consumers, and "applauding health staff and front-line workers" common narratives. A similar study in Australia found the same level of COVID-washing in social media posts, whereby one-third of all posts by the "Big Food and Drinks" brands during the same 4-month period were COVID-19 related, and fast-food companies were also the largest proponents of COVID-washing (31). The COVID-19 pandemic provided an opportunity for food and beverage companies to market themselves as caring and contributing members of a society during a time of unprecedented crisis, and thereby increase the desirability of their brands and the products they sell.…”
Section: Covid-washing By New Zealand's Major Food and Drinks Brandssupporting
confidence: 52%
“…This is arguably when many viewers would be most vulnerable to "comfort" or binge eating due to the jubilation of being out of lockdown and relief at the end of a prolonged period of heightened stress caused by the pandemic (36)(37)(38). The COVID-related themes commonly used by unhealthy food and drink brands in social media posts were analogous to those found in studies globally (17,31), with "community support, " positioning themselves as "in this together" with consumers, and "applauding health staff and front-line workers" common narratives. A similar study in Australia found the same level of COVID-washing in social media posts, whereby one-third of all posts by the "Big Food and Drinks" brands during the same 4-month period were COVID-19 related, and fast-food companies were also the largest proponents of COVID-washing (31).…”
Section: Covid-washing By New Zealand's Major Food and Drinks Brandsmentioning
confidence: 61%
See 3 more Smart Citations